Managing library volunteers : a practical toolkit - Driggers, Preston F. (Preston Franklin), 1940- (American Library Association, 2002)
Volunteers play a vital role in successful libraries across the county, and as staffing budgets shrink and change, it is more important now than ever to create and sustain a volunteer program that works to your advantage. This hands-on guide to recruiting, training, managing, and recognizing library volunteers is packed with ideas that will help you to both start from scratch or reenergize the system you already have. It is a must-have for any size or type of budget-savvy, proactive library. Organized around the timeline of the volunteer recruitment process, this practical toolkit covers the g.